Calculation of the sensitivity of active thermal inspection on the basis of solving an unidimensional problem of heating a three-layer sheet with a constant heat flow; The Soviet journal of nondestructive testing; Vol. 22, iss. 6 - Vavilov V. P. Vladimir Platonovich (1986, 1986)
An analytical solution was obtained for the unidimensional problem of thermal inspection for a defect with arbitrary thermophysical properties and thickness. Part of the table for calculating the sensitivity of inspection is presented; the table links, in the dimensionless form, the parameters of the temperature field. An example of calculations is given.